The Evolution of Collaboration Skills Research in Education : Trends, Intellectual Structure, and Research Topics - Kusumarti, Diah Galuh; Sariyatun, Sariyatun; Rejekiningsih, Triana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2024)
This study aims to examine the evolution of collaboration skills in the field of education including publication trends, intellectual structure, and research topics. This study uses the bibliometric method which is part of the literature review, with descriptive data analysis. Analysis was carried out on 723 documents from the Scopus database that had been selected. The results show that the trend of document publications on collaboration skills began to increase at the beginning of the 2001s until reaching the highest number of publications in 2023 with 104 documents. In the early period (1986-2004), there were five schools of thought that became the foundation of its intellectual structure, namely the practice of collaboration, small group learning, learning theory and its implementation, software design, and engineering studies. Meanwhile, in the next period (2005-2023) there are learning theory and its implementation, collaborative learning, interprofessional education, cooperative learning, and computer-supported learning. If the schools of thought in the two periods are compared, it can be seen that there has been an evolution of the intellectual structure of collaboration skills. Evolution also occurred in the collaboration skills research topics, which can be seen from the keywords data that often appeared in the early period, namely active learning, communication skills, and cooperative learning. In the following period, it changed to collaboration, interprofessional education, and higher education. These research findings can provide information regarding the knowledge base of collaboration skills and related research topics that have been carried out.